A multiprofessional perspective on the principal barriers to universal health coverage and universal access to health in extremely poor territories: the contributions of nursing - Viviane Helena de França; Celina Maria Modena; Ulisses Eugenio Cavalcanti Confalonieri
Objective: to investigate the knowledge of managers and health professionals, social workers and education professionals regarding the principal barriers to universal health coverage and universal access to health on the part of the extremely poor population; and to point to the contributions made by nursing for the promotion of this right. Method: a qualitative study whose reference was, for ensuring the right to health, the reorientation of the Brazilian Unified Health System (SUS) towards universal coverage and access in these territories. Interviews were held with 27 members of the multi-professional team of a municipality with high social vulnerability. The data were worked on using thematic content analysis. Results: the following were ascertained as the principal barriers to universal health coverage and access to health: failures in the expansion and strengthening of the services; absence of diagnosis of the priority demands; shortage of technology, equipment, and material and human resources; poor local infrastructure; and actions with low resolutive power and absence of interdepartmental policies. Within the multi-professional team, nursing acts in the SUS in unique health actions and social practices in these territories, presenting an in-depth perspective on this harsh reality, being able to contribute with indispensable support for confronting these disparities in universal health coverage and universal access to health. Conclusion: nursing's in-depth understanding regarding these barriers is essential for encouraging the processes reorienting the SUS, geared towards equality in the right to health.